Profil dan Visualisasi Kata Kunci Media Pustakawan dan Visi Pustaka Periode 2017-2021 - Suhendani Suhendani; Rochani Nani Rahayu (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Profile and visualization of the keywords Media Librarian and Library Vision for the 2017-2022 period were carried out using the Bibliometric method. The research objectives were to determine: 1. The number of articles published in both journals during 2017-2022; 2. Authors who contributed to the two journals, and 3. Keyword profiles and visualization using Vosviewer. Data were taken from both journal sites, namely https://ejournal.perpusnas.go.id. The data collected is the number of articles, authors and keywords used in both journals. The results and conclusions of the research are that Media Librarian has 135 articles from 18 publications, more than the Visi Pustaka journal, which has 135 article titles from 15 publications. Authors who contributed to Librarian Media and Library Vision were 204 authors and 158 authors, respectively. Vision Pustaka published regularly and regularly compared to Media Librarians. The publication with the most authors in the Media Librarian journal is in vol. 26 no. 4, 2019, with as many as 16 authors, while in the Librarian Vision journal, it is in vol. 23 no. 2, 2021, with as many as 15 authors. The highest number of writers is common, with Media Librarians with 15 writers. The number of occurrences of different keywords in Vision Reader is 292 out of the existing keywords 395. In contrast, the keywords in Media Librarian are more numerous than the keywords in Vision Library, with different keywords of 370 of the number of keyword occurrences. There were 607 of them. The resulting phrases or keywords that were often used in Vision Library appeared 148 times out of 37 different keywords generated, including Library/Library appearing 21 times (0.14%), Bibliometrics appearing 19 times (0 .13%), and Librarian/Librarian appeared 14 times (0.09%). Phrases or keywords that are often used in Librarian Media appear 222 times out of 31 different keywords, including Librarian/Librarian appearing 41 times (0.18%), Bibliometrics appearing 23 times (0.10%), and Library/Library appearing 19 times (0.09%). The two journals, both Media and Librarian Visi Pustaka, have the same phrases or keywords used. Visualization of the emergence of the title and abstract keywords in both journals produces the same topic by dominating the topics discussing libraries, Indonesia, librarians, users and information and connecting them with keywords in other clusters. The least discussed keywords relate to user anxiety, pandemic, information needs, users and analysis of digitalization, innovation, digital era, library collection and digital library. It is suggested that keywords that occur a little can be used as a topic for further research as a novelty in writing in the field of libraries.